Too Expensive to Treat? Non-Treatment Decisions at the Margins of Viability. (13th November 2018) - Flessas, Tatiana; Jackson, Emily
Abstract: This article seeks to challenge the assumption that it is legitimate to consider the costs of premature babies' future social and educational needs when deciding what treatment, if any, to provide in the neonatal intensive care unit (NICU) . It questions the elision that is made between the claim that a particular treatment is insufficiently cost-effective and the claim that a person will be a burden on the state in the future. It discusses a series of common misunderstandings about how treatment decisions are taken in the NICU and concludes by suggesting that the claim that premature babies are too expensive to treat may depend upon regarding a premature infant as if she were not yet a person, with rights and interests of her own.